After The Fact Interactive: USDA government Inspected (Nation of nations: a concise narrative of the American Republic) - James West Davidson...[et.al.] (MC Graw Hill Companies, 2001)
File dalam bentuk Video (Quicktime), Flash, Gambar, Htm (Internet), dll; Isi: ATF (Flash, Nonflash, dll), Data, Images, Install (Acrobat, Exploler, Flash, dan Quicktime), dll; Judul Dalam Kemasan.